The thickness of the cortical bone in different maxillae using medical images - Fonseca, E.M.M. (2010)
The aim of this study was to investigate whether there is a relationship between the thickness of the cortical bone of mandible human and the age and the sex of patient. In this work the measure of the cortical bone thickness was obtained in different computed tomography (CT). Different human mandibles were scanned using high resolution micro-CT instrument in which many axial slices were obtained. A total of four medical images were studied and observed. Two different groups were characterized. The first one, with two female maxillae (F): an old and a young patient. The second group of two males mandibles (M), with similar age. A comparison between the male and female sex was also obtained. The cortical bone thickness of the mandible may be affected by tooth extraction, age and sex patient. The use of this type of information is useful for complementary diagnostic information and treatment planning.